Reverse discourse completion task as an assessment tool for intercultural competence - Kanik, Mehmet (Studies in Second Language Learning and Teaching, 2013)
This paper proposes a prototypic assessment tool for intercultural communicative competence. Because traditional discourse completion tasks (DCTs) focus on illocutionary competence rather than sociolinguistic competence, a modified version of a DCT was created to target sociolinguistic competence. The modified DCT employs speech acts as prompts and asks respondents to write about a situation in which a given speech act would be appropriate. This new tool is named a reverse discourse completion task (R-DCT). The task was given to learners of Turkish as a second language. Data from 12 participants were analyzed for their provision of sociopragmatic factors such as power, distance and imposition and also with respect to whether the situation was relevant to a given speech act. Responses from the participants show that R-DCTs can be used to assess intercultural competence as they help reveal respondents’ knowledge of sociolinguistic context in which a given speech act may be appropriate. By removing the need for comparison with native speaker data and the limitations that emerge from the lack of linguistic formula at respondents’ disposal, R-DCT is a promising elicitation task to assess sociolinguistic competence, an integral part of Byram’s (1997) model of intercultural communicative competence.